2006
DOI: 10.1002/pssc.200668095
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo analysis of electronic noise in semiconductors under sub‐terahertz cyclostationary mixed fields

Abstract: This paper reports the results of Monte Carlo simulations of electronic noise in a GaAs bulk driven by two mixed high-frequency large-amplitude periodic electric fields. Under these conditions, the system response shows some peculiarities in the noise performance, such as a resonant-like enhancement of the spectra near the two frequencies of the applied fields. The relations among the frequency response and the velocity fluctuations as a function of intensities and frequencies of the sub-terahertz mixed excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…In a previous paper we have examinated the dependence of the frequency response and of the velocity fluctuations by the intensities of the mixed excitation fields with the aim to establish if the wave-mixing could cause an enhancement or a suppression of the noise level. We have found that the level and the peaks in the noise spectra are very sensitive to the amplitude of the excitation signals [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper we have examinated the dependence of the frequency response and of the velocity fluctuations by the intensities of the mixed excitation fields with the aim to establish if the wave-mixing could cause an enhancement or a suppression of the noise level. We have found that the level and the peaks in the noise spectra are very sensitive to the amplitude of the excitation signals [7].…”
Section: Introductionmentioning
confidence: 99%
“…The spectral density of the electron velocity fluctuations in a n-type GaAs bulk undergoes critical modifications under the action of two mixed highfrequency large-amplitude periodic electric fields [1][2][3]. In particular, recent studies based on Monte Carlo simulations have shown that the total power of the intrinsic noise is very sensitive to the amplitude and the frequency of the excitation signals and that wave-mixing conditions may give rise to a mere redistribution, an enhancement or a suppression of the noise level, depending on the constructive interplay between the two excitation fields.…”
Section: Introductionmentioning
confidence: 99%